EDUCATION ON ECOLOGICAL VALUES (Conferencea, 2023)
Environmental values play an important role in improving the ecological environment, protecting nature, and at the same time strengthening people's health. In this written article, we talk about bringing ecological values to a higher level, regularly connecting them with our daily lifestyle. At the same time, some types of activities that should be transformed into ecological values were discussed.